Fulfillment Matter of Education Rights of Children in Conflict With the Criminal Law - Nurhamdah Nurhamdah; Emilia Mustary; Fikri Fikri; Subhan Saleh; Nabilahumaida Nabilahumaida (IAIN Manado, 2022)
This study aims to determine the forms of the fulfillment of education rights for children in conflict with the criminal law in Indonesia through the